Simulated Microgravity and Recovery-Induced Remodeling of the Left and Right Ventricle - Zhong, Guohui; Li, Yuheng; Li, Hongxing; Sun, Weijia; Cao, Dengchao; Li, Jianwei; Zhao, Dingsheng; Song, Jinping; Jin, Xiaoyan; Song, Hailin; Yuan, Xinxin; Wu, Xiaorui; et al. (Frontiers in Physiology, 2016)
Physiological adaptations to microgravity involve alterations in cardiovascular systems. These adaptations result in cardiac remodeling and orthostatic hypotension. However, the response of the left ventricle (LV) and right ventricle (RV) following hindlimb unloading (HU) and hindlimb reloading (HR) is not clear and the underlying mechanism remains to be understood. In this study, three groups of mice were subjected to HU by tail suspension for 28 days. Following this, two groups were allowed to recover for 7 or 14 days. The control group was treated equally, with the exception of tail suspension. Echocardiography was performed to detect the structure and function changes of heart. Compared with the control, the HU group of mice showed reduced LV-EF (ejection fraction) and LV-FS (fractional shortening). However, mice that were allowed to recover for 7 days after HU (HR-7d) showed increased LVIDs (systolic LV internal diameter) and LV Vols (systolic LV volume). Mice that recovered for 14 days (HR-14d) returned to the normal state. In comparison, RV-EF and RV-FS didn’t recover to the normal conditions till being reloaded for 14 days. Compared with the control, RVIDd (diastolic RV internal diameter) and RV Vold (diastolic RV volume) were reduced in HU group and recovered to the normal conditions in HR-7d and HR-14d groups, in which groups RVIDs (systolic RV internal diameter) and RV Vols (systolic RV volume) were increased. Histological analysis and cardiac remodeling gene expression results indicated that HU induces left and right ventricular remodeling. Western blot demonstrated that the phosphorylation of HDAC4 and ERK1/2 and the ratio of LC3-II / LC3-I, were increased following HU and recovered following HR in both LV and RV, and the phosphorylation of AMPK was inhibited in both LV and RV following HU, but only restored in LV following HR for 14 days. These results indicate that simulated microgravity leads to cardiac remodeling, and the remodeling changes can be reversed. Furthermore, in the early stages of recovery, cardiac remodeling may be intensified. Finally, compared with the LV, the RV is not as easily reversed. Cardiac remodeling pathways, such as, HDAC4, ERK1/2, LC3-II and AMPK were involved in the process.